Study of Converted-Wave Modeling: AVO Application for Shallow Gas Models - Natashia Christy Viony; Wahyu Triyoso (Himpunan Ahli Geofisika Indonesia (HAGI), 2018)
The application of converted-wave seismic method in hydrocarbon exploration has increased significantly. Since the conventional seismic ceases to provide an adequate result in complex geology area and it provides an ambiguous brightspot response. The main principle is that an incident P-wave produces reflected and converted P and SV wave when the downgoing P-wave impinges on an interface. Converted-wave seismic uses the multicomponent receiver that records both of vertical component and horizontal component. The vertical component is assumed to correspond to the compressional PP wave and the horizontal correspond to the PS converted-wave. In this research, a synthetic model with the shallow gas and the salt dome below are constructed. The purpose of this study is to analyze the brightspot due to the presence of shallow gas and its effect to the quality of PP and PS wave reflection below the gas zone. To achieve the goal, both vertical and horizontal seismic data processing are performed. In horizontal data processing, the best gamma function (Vp/Vs) value is estimated to produce the better and reliable image. The result shows that the brightspot response in conventional data doesn’t exist in converted-wave data and the imaging below the gas zone in converted-wave data is better than the conventional due to the attenuation and diffraction effect that caused by gas column. Processing is followed by AVO analysis to compare the AVO response of PP and PS data in characterizing gas reservoir. Both PP and PS AVO curve shows the consistency with synthetic AVO from well data. Gas reservoir is a class 1 AVO anomaly with positive intercept and negative gradient on PP data. However, PS AVO curve does not refer any anomaly. It is because S-wave is not sensitive to the existence of rock saturant.